New approach to the resolution of triangular fuzzy linear programs: MOMA-plus method. - COMPAORE, Abdoulaye; SOME, Kounhinir; SOME, Blaise (International Journal of Applied Mathematical Research, 2017)
In this  paper,  we propose  a  new  approach to  the  resolution of linear  programs,  whose coefficients are fuzzy triangular numbers.  This new approach is an adaptation from the method MOMA-plus (Multi-Objective Metaheuristic based on Alienor method) [1] to the resolution of fuzzy linear programs. First of all it consists in using of a new procedure proposed here to the converting of the fuzzy linear program into a deterministic multi-objective linear program, secondly  of the  using  of the  MOMA-plus  procedure for resolution.  Finally, three numerical examples are given  to  explain   the  procedures and  highlight  the performances of  this  new approach.